The influence of the fuel cell by temperature and the design of control system of temperature - Qi, Yi (2017)
Operating temperature is one of the most important factors affecting the fuel cell performance. Increase of the operating temperature can improve the rate of chemical reaction, however, it reduces the humidity in the proton exchange membrane leading to reduce its performance. This project is to study the optimal working temperature of proton exchange membranes fuel cell (PEMFC), through testing of fuel cell perfom1ance in different temperature in order to find the most suitable temperature for the low temperature PEMFC. Meanwhile, this project combines other factors, such as gas pressure, purging time and water molecule on membranes, which can also affect the perfom1ance of fuel cell are under investigation. Besides, this project implemented automatic control of the fuel cell system by using Lab VIEW. Through controlling external cooling system of fuel cell by PID control algoritlun, this project designs a full -automation temperature control system for PEMFC with low parasitic loss to achieve the best output power of the fuel cell. Furthermore, this study includes setting up a complete fuel cell system, allowing all sub-components in the system integrated in a moveable working platform. It is ready to be used as a demonstration system for chemical industries, where hydrogen is available as a byproduct from the chemical plant.